Making a splash: A closer look at early specialization in competitive diving - Lenz, A.; Provance, B.; Provance, A. (Current Sports Medicine Reports, 2024)
This review article explores the multifaceted aspects of early specialization in diving, focusing on its implications for injury prevalence, performance, and mental health. It highlights the increasing trend of early specialization driven by ambitions for collegiate and Olympic success, despite recommendations advocating for diversification. Divers are at risk for acute and overuse injuries, particularly during high-velocity water entries; however, data on injury patterns, especially among elite divers and early specializers, remains scarce. Recent data suggest a correlation between early specialization and reduced rates of certain injuries among youth divers, but distinguishing between acute and overuse injuries is crucial. Additionally, early specialization may pose mental health risks, with divers facing pressures related to performance, body image, and parental expectations. This article underscores the need for tailored guidelines to mitigate injury risks and promote holistic well-being among youth divers, recognizing the complex interplay between physical and psychological factors in sports specialization.